Potensi Ekstrak Etanol Seledri (Apium graveolens) untuk Maskulinisasi Ikan Cupang (Betta sp) - Awaludin Awaludin; Diana Maulianawati; Muhammad Adriansyah (Jurnal Sumberdaya Akuatik Indopasifik, 2019)
Betta fish is one of the excellent ornamental fish because it has high economic value. Betta fish that have economic value are male betta fish because it has a beautiful shape. To increase male fish production, steps can be done by masculinization. This study aims to determine the effect of celery extract on the percentage of male betta fish by masculinization. This study uses a completely randomized design (CRD) with 6 treatments and 3 replications. The treatment in this study was 7-day-old betta fish larvae soaked in celery extract media with different concentrations for 8 hours. The treatment is the addition of celery extract as much as 5 mg / L (P1), 10 mg / L (P2), 20 mg / L (P3), 40 mg / L (P4), 80 mg / L (P5) and without the addition of celery extract as a control (P0). Based on phytochemical testing, celery ethanol extract contains steroids, flavonoids, tannins, and phenols. The results showed that the addition of celery extract with different concentrations had a significant effect on the percentage of male betta fish, but there was no significant effect on survival rates.